KEBERHASILAN AKADEMIK SEBAGAI KONSTRUKSI SOSIAL: KOMPETENSI GURU, NEGOSIASI MAKNA KEBIASAAN BELAJAR, DAN LINGKUNGAN PRODUKTIF DI SMA - Muhammad Yusron Maulana El-Yunusi; Muhammad Imam Asrofi (Hijri, 2026)
This literature study aims to analyze the social construction of academic success in senior high school through the role of teacher competence as authority figures, the negotiation of study habits meaning among peers, and the interpretation of the learning environment as a productive space. The method used is qualitative library research with a thematic synthesis approach following systematic literature review procedures from a constructionist perspective. The results indicate that teacher competence extends beyond subject mastery to include the ability to build personal relationships and create a supportive classroom climate. Teacher authority voluntarily recognized by students becomes the foundation for internalizing academic values. Peers form an arena of negotiation where the meaning of study habits and achievement are collectively interpreted through daily interactions, creating group norms that can either support or hinder academic attainment. The learning environment is interpreted as a productive space when students feel psychologically safe, intellectually challenged, supported by positive relationships, and have access to adequate learning resources. These three aspects are interconnected and collectively construct the social reality that shapes how students perceive, pursue, and achieve academic success. This study contributes theoretically to enriching educational sociology and social psychology literature with a constructionist perspective on academic achievement.